Modelo de planeación financiera para una empresa de transporte público de una ciudad pequeña (2017)
The following document is an analysis to the company providing public transport service Autobuses del Sur SA, from the social, environmental and economic and financial relevance, where the costs associated with its operation will be evaluated one by one. With the actual extracts of a bus from each of the routes as shown, it was extrapolated in order to determine the income and expenses of the company as a whole, analyzed and described every two weeks because it is the payment method to owners of the vehicles, then the information of the 4 routes was compiled and a cost study was developed with the objective of determining the price of moving a passenger in one day and for each kilometer traveled.